Galatians 3 and the redefinition of the criteria of covenant membership in the new faith-era in Christ - Toit, Philip la G. du (Neotestamentica, 2018)
This article firstly evaluates the Radical New Perspective on Paul and the Messianic Judaist approach to the letter to the Galatians, which can be seen as similar approaches. In these approaches, the rhetoric in the letter to the Galatians is perceived to be directed to gentile believers only, which converges with the view that a continuing distinction between gentile and Judaean believers is upheld in the Pauline corpus. This evaluation involves testing this kind of approach in terms of its methodology and implications, with a specific focus on Paul's use of the first person singular and first person plural in the letter. Secondly, in answer to the above evaluation, the criteria for identity and covenant membership are pursued by focusing on Gal 3. The Spirit-flesh contrast, which converges with the faith-works contrast, as well as the contrast between the new era in Christ and the eschatologically old era under the Law, is argued to be the controlling paradigm for determining identity and covenant membership in the letter. Although this new identity stands in continuity with the promise to Abraham, it is understood in a redrawn and renewed way. Believers' position toward the Law and Paul's rhetorical aims in Gal 3 are reconsidered in light of the above.